The first women photographers in Aragon: pioneers and modern - Agustín Lacruz, Mª del Carmen; Tomás Esteban, Sandra (Revista General de Información y Documentación, 2018)
The objective of this work is to study, outside the category of anecdote or marginal phenomenon, the presence and participation of women in the development of the photographic medium in Aragon. The reconstruction of his biographies and the characterization and contextualization of his professional trajectories has been carried out through the analysis and systematic review of the sources of information located to date, both of hemerographic, bibliographic and documentary nature. Among others, aragonese photographers are studied Poland Sanz, Madame Senges, Dolores Gil, María Cardarelly, Tomasa Chinar, Ana María Lapetra, Ángeles Buil, petra Tena, Prima Gavilanes, Silveria Fañanás, Petra Sabaté, Matilde López, Carmen Jarque, Rosario de la Fuente, Asunción Pascual, Divina Campo, Teresa Gallifa, Margot Autié and Josefa Farina.
Keywords: Women photographers; Cultural studies Gender studies; History of photography; Aragonese photographers; Aragón.